Preface to the special issue on integrated research of atmosphere, ecosystems and environment at Pallas - Lohila, Annalea; Penttilä, Timo; Jortikka, Sinikka; Aalto, Tuula; Anttila, Pia; Asmi, Eija; Aurela, Mika; Hatakka, Juha; Hellén, Heidi; Henttonen, Heikki; Hänninen, Pekka; Kilkki, Juho; et al.
2015